Edukasi Pencegahan Infeksi Saluran Kemih pada Masyarakat Lanjut Usia di Desa Nagrak - Effendi, Ida; Samira, Jihan; Bella, Isa; Amalia, Husnun (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Health problems caused by aging can affect every aspect of life. The number of urinary tract infections (UTI) in the elderly in Indonesia is increasing. There are many risk factors in the elderly that make the incidence of UTI is quite high, such as comorbid diseases, nutritional status, cognitive impairment and water intake. Community service activities (PkM) are carried out with the aim of improving the health status of the elderly. Education was held on December 3rd ,2023 at the Trisakti campus field, Nagrak Bogor, West Java, targeting people from the pre-elderly and elderly groups. UTI education is provided by presenting information about the signs and symptoms of urinary tract infections, how to prevent urinary tract infections and things to pay attention. A total of 26 participants consisting of 13 men and 13 women participated in this activity. The most age category of participants was in the pre-elderly category (76.92%). At the end of the activity, the knowledge of urinary tract infections increase by 73.08%. An increase in understanding of UTI definition by up to 15.36%, UTI symptoms by up to 15.42% and UTI risk factors by up to 30.77%. This activity gives benefits to be held sustainably so that the elderly community in Nagrak can improve their health status